(untitled) (Annals of Medical Research, 2023)
Aim: Fragile X syndrome (FXS) is a rare genetic disease that can have several intellectual and developmental disabilities. Here, we aim to examine psychopathology in children with FXS and investigate the relationship between children’s psychosocial well-being and socio-demographic factors, autism spectrum disorder (ASD) comorbidity, and the type and level of caregivers’ perceived social support. Materials and Methods: Twenty-six children aged 5-18 years with FXS and 26 age- and sex-matched healthy controls (HC) were included. DSM-5-based clinical interviews were conducted with all participants. We also collected parent ratings of health-related quality of life indexes and perceived social support levels and types. Results: The mean age of children with FXS was 10.9 ± 3.5 years, and the mean age of healthy comparisons (HC, n= 26) was 11.8 ± 2.6 years. In the FXS group, 84.6% had comorbid psychiatric disorders, and 65.3% had intellectual disability. FXS group displayed lower psychosocial and total quality of life scores than the HC group. Also, there was significant positive correlations between children’s’ psychosocial well-being and "significant others" (rp = 0.502, p = 0.009) and total perceived support scores (rp = 0.448, p = 0.022). The most influential factor related to the psychosocial well-being in children with FXS was ASD comorbidity (F= 30.6, R2, 0.543, p<0.001). Conclusion: Providing support to mothers of children with FXS may positively affect the children’s health outcomes, especially psychosocial well-being.